Botulinum Toxin Type A for Trigeminal Neuralgia: A Comprehensive Literature Review - Yan Tereshko; Simone Dal Bello; Christian Lettieri; Enrico Belgrado; Gian Luigi Gigli; Giovanni Merlino; Mariarosaria Valente (Toxins)
Trigeminal neuralgia is a neuropathic pain syndrome responsive to botulinum toxin type A therapy. This review had the goal of analyzing the different studies published from 2002 to January 2024 to better define the techniques and the types of botulinum toxin type A used, the doses, the injection routes, and the different populations of trigeminal neuralgia patients treated. We considered only articles in which the therapy was administered to humans to treat trigeminal neuralgia. Case reports, case series, open-label, retrospective, and RCT studies were considered. The research was conducted on MEDLINE and the keywords included (trigeminal neuralgia) and (botulinum). Thirty-five articles were considered suitable for this review. Botulinum toxin type A was shown to be an effective therapy for TN pain in all the articles analyzed, albeit there is a lack of standardization in methods and outcomes. The techniques, the doses, and the injection approaches were very heterogeneous among the studies. Only two botulinum toxin type A formulations have been used in this setting: onabotulinumtoxinA and lanbotulinumtoxinA. There were 300 patients treated with onabotulinumtoxinA and 760 treated with lanbotulinumtoxinA overall (in 42 patients, the formulation was not specified). The distinction between etiological and clinical types of TN has been made by only a small portion of the studies. The main adverse event was transient facial asymmetry. Botulinum toxin type A is indeed a promising therapy that is clearly effective for trigeminal neuralgia. OnabotulinumtoxinA is the most common formulation used in Western countries; however, the meager sample of TN patients treated, and the lack of standardization are not sufficient for this therapy to be approved by the FDA or EMA. Indeed, more studies with standardized methods and larger samples are needed for this purpose.